Numerical investigation of flare gas combustion in ethylene cracking furnaces - Rashed Al-ajmi (19932174) (2025)
Flaring of natural gas at oil and gas fields is a significant environmental concern, leading to wasted resources, greenhouse gas emissions, economic costs, and high noise levels. Significant economic and environmental benefits can be achieved if flare gas is used as a fuel in ethylene cracking furnaces. This study investigates the feasibility of utilizing recycled flare gas as a fuel in ethylene cracking furnaces, focusing on managing flare abnormalities. Using ANSYS Fluent to simulate a low-NOx burner, the study examines the impact of varying heat flux levels, flare gas mixtures, and fuel mass flow rates on furnace performance, emphasizing temperature profiles, flame stability, and combustion dynamics. The analysis highlights the complex, non-linear responses of combustion to varying flare gas compositions and flow conditions, underscoring the influence of specific hydrocarbons and fuel supply on burner efficiency. Positioned within the environmental and economic context of Qatar and Gulf countries, the findings provide innovative insights into optimizing industrial processes, enhancing environmental sustainability, and improving flare gas utilization in ethylene cracking furnaces. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2024.133381